Placenta Growth Factor in Eyes with Neovascular Glaucoma Is Decreased after Intravitreal Ranibizumab Injection. - Minwen Zhou; Jiawei Wang; Wei Wang; Wenbin Huang; Xiaoyan Ding; Xiulan Zhang (PLoS ONE, 2016)
PURPOSE:To evaluate changes in the concentrations of placental growth factor (PlGF) and vascular endothelial growth factor-A (VEGF-A) in aqueous humor of patients with neovascular glaucoma (NVG) before and after an intravitreal injection of ranibizumab (IVR) and to determine the underlying correlation between the levels. METHODS:The prospective interventional comparative study involved 20 eyes of 20 patients with surgery-required advanced NVG and 20 control subjects from January 2013 to November 2013. The NVG eyes received the IVR treatment before glaucoma surgery. Aqueous humor was collected at the time of the IVR injection (pre- IVR) and at the time of antiglaucomatous surgery (post-IVR). Aqueous humor was also collected at the time of cataract surgery in normal control. Aqueous humor and plasma VEGF-A and PlGF levels were measured with an enzyme-linked immunosorbent assay methods, respectively. RESULTS:The mean aqueous humor PlGF and VEGF-A concentrations in the pre-IVR eyes were significantly higher than in those of the control subjects (p<0.001), whereas the plasma levels showed no significant difference. There was a statistically significant correlation between the aqueous humor PlGF and the VEGF-A concentration (r = 0.612, p = 0.003). The mean aqueous humor PlGF in the post-IVR eyes dramatically decreased from 1078.36 ± 755.83 to 177.64 ± 151.73 pg/mL (p<0.001). The VEGF-A level showed a similar trend from 3697.64 ± 2104.47 pg/mL to 183.54 ± 130.35 pg/mL (p<0.001). CONCLUSIONS:Aqueous humor concentrations of VEGF-A and PlGF were significantly elevated in the eyes with NVG, and there was a positive correlation between the levels. After an IVR treatment, VEGF-A and PlGF were significantly decreased in NVG eyes.